ANALISIS PEMASARAN RUMPUT LAUT DI DESA LALOMBI KECAMATAN BANAWA SELATAN KABUPATEN DONGGALA SULAWESI TENGAH - Saprianti, Saprianti; Laapo, Alimudin; Howara, Dafina (AGROTEKBIS, 2016)
The aim of this study was to observe the form of seaweed marketing chain, the amount of margin in each marketing chain, and seaweed marketing efficiency in each marketing chain. Respondents selected as sample were seaweed farmers and a trader. Samples of seaweed farmer were chosen by using simple random sampling method. There were 25 respondents interviewed from the total of 50 population. Sample of trader respondent was chosen by using tracing sampling method, and there was 1 trader respondent interviewed. The total number of respondents interviewed was 26 respondents. Result of marketing analysis showed that marketing margin observed in chain I was IDR 4.500; and no marketing margin was observed in chain II because seaweeds were directly sold to cunsumers. Marketing chain of seaweed in Lalombi village consisted of two chains, namely:1. Seaweed Farmer â Traderâ Consumer.2. Seaweed Farmer â Consumer.In the first chain, selling price received by seaweed farmers was 60% with the efficiency value was 40%. In the second chain, selling price received by seaweed farmers was 100% with the efficiency value was 0%; and therefore seaweed marketing chain more efficient was the second marketing chain.Key Words: Marketing analysis, seaweed.